Within The Context of An Online TBLL Environment, Enhancing the Negotiationof Meaning Through Task Familiarity Through the Utilization of Subtitled Videos - Rabia Jalil ,; Shadab Ahmad ,; Shadab Ahmad , (Spectrum of Engineering Sciences, 2024)
Through the utilization of subtitled films, this study investigates the influence that taskfamiliarity has on the process of meaning negotiation within the context of an online task-basedlanguage learning (TBLL) environment. The purpose of this research is to investigate the extentto which non-native speakers (NNSs) negotiate meaning in an effort to hasten the processof learning a second language and improve the ability to comprehend input. By utilizingachatcapability in WebCT-Vista and an online TBLL environment that was designed specificallyforthis research, ten NNS-NNS dyads worked together to complete four communicative tasks. There were five pairs of students who were shown videos with subtitles before theywererequired to complete the activity. The remaining five pairs of students completed the taskswithout watching the videos. The level of meaning negotiation was determined by Smith(2003)by employing a variant of Gass and Varonis's (1985) negotiation of meaning sequences model foronline communication. This model was specifically designed for online communication. Theinformation that was collected from the transcripts of the conversations revealed that non-native speakers (NNSs) who had a greater level of familiarity with the tasks engagedinmoreextensive meaning negotiation in comparison to those who did not have such familiarityaboutthe tasks.